d-Alanylation of Lipoteichoic Acids in Streptococcus suis Reduces Association With Leukocytes in Porcine Blood - Öhlmann, Sophie; Krieger, Ann-Kathrin; Gisch, Nicolas; Meurer, Marita; de Buhr, Nicole; von Köckritz-Blickwede, Maren; Schütze, Nicole; Baums, Christoph Georg (Frontiers in Microbiology, 2022)
Streptococcus suis (S. suis) is a common swine pathogen but also poses a threat to human health in causing meningitis and severe cases of streptococcal toxic shock-like syndrome. Therefore, it is crucial to understand how S. suis interacts with the host immune system during bacteremia. As S. suis has the ability to introduce D-alanine into its lipoteichoic acids (LTAs), we investigated the working hypothesis that cell wall modification by LTA D-alanylation influences the interaction of S. suis with porcine blood immune cells. We created an isogenic mutant of S. suis strain 10 by in-frame deletion of the D-alanine D-alanyl carrier ligase (DltA). D alanylation of LTAs was associated with reduced phagocytosis of S. suis by porcine granulocytes, reduced deposition of complement factor C3 on the bacterial surface, increased hydrophobicity of streptococci and increased resistance to cationic antimicrobial peptides. At the same time survival of S. suis was not significantly increased by LTA D-alanylation in whole blood of conventional piglets with specific IgG. However, we found a distinct cytokine pattern as IL-1β but not TNF-α levels were significantly reduced in blood infected with the ΔdltA mutant. In contrast to TNF-α, activation and secretion of IL-1β is inflammasome-dependent, suggesting a possible influence of LTA D-alanylation on inflammasome regulation. Especially in the absence of specific antibodies, the association of S. suis with porcine monocytes was reduced by D-alanylation of its LTAs. This dltA dependent phenotype was also observed with a non-encapsulated dltA double mutant indicating that it is independent of capsular polysaccharides. High antibody levels caused high levels of S. suis – monocyte – association followed by inflammatory cell death and strong production of both IL-1β and TNF-α, while the influence of LTA D-alanylation of the streptococci became less visible. In summary, the results of this study expand previous findings on D-alanylation of LTAs in S. suis and suggest that this pathogen specifically modulates association with blood leukocytes through this modification of its surface.